The emerging invasive alien plants of the Drakensberg Alpine Centre, southern Africa - Carbutt, C. (African Biodiversity & Conservation, 2012)
An ‘early detection’-based desktop study has identified 23 taxa as ‘current’ emerging invasive alien plants in the Drakensberg Alpine Centre (DAC) and suggests a further 27 taxa as probable emerging invaders in the future. These 50 species are predicted to become problematic invasive plants in the DAC because they possess the necessary invasive attributes and have access to potentially suitable habitat that could result in them becoming major invaders. Most of the ‘current’ emerging invasive alien plant species of the DAC are of a northern-temperate affinity and belong to the families Fabaceae and Rosaceae (four taxa each), followed by Boraginaceae and Onagraceae (two taxa each). In terms of functional type (growth form), most taxa are shrubs (9), followed by herbs (8), tall trees (5), and a single climber. The need to undertake a fieldwork component is highlighted and a list of potential study sites to sample disturbed habitats is provided. A global change driver such as increased temperature is predicted to not only result in extirpation of native alpine species, but to also possibly render the environment more susceptible to alien plant invasions due to enhanced competitive ability and pre-adapted traits. A list of emerging invasive alien plants is essential to bring about swift management interventions to reduce the threat of such biological invasions.